Hepatic MyD88 regulates liver inflammation by altering synthesis of oxysterols - Lefort, Charlotte (Am J Physiol Endocrinol Metab, 2019)
This study aimed to investigate the function of hepatic myeloid differentiation primary response gene 88 (MyD88), a central adaptor of innate immunity, in metabolism. Although its role in inflammation is well known, we have recently discovered that MyD88 can also mediate energy, lipid, and glucose metabolism. More precisely, we have reported that mice harboring hepatocyte-specific deletion of MyD88 (Myd88(ΔHep)) were predisposed to glucose intolerance, liver fat accumulation, and inflammation. However, the molecular events explaining the onset of hepatic disorders and inflammation remain to be elucidated. To investigate the molecular mechanism, Myd88(ΔHep) and wild-type (WT) mice were challenged by two complementary approaches affecting liver lipid metabolism and immunity. The first approach consisted of a short-term exposure to high-fat diet (HFD), whereas the second was an acute LPS injection. We discovered that upon 3 days of HFD Myd88(ΔHep) mice displayed an increase in liver weight and liver lipids compared with WT mice. Moreover, we found that bile acid and oxysterol metabolism were deeply affected by the absence of hepatic MyD88. Our data suggest that the negative feedback loop suppressing bile acid synthesis was impaired (i.e., ERK activity was decreased) in Myd88(ΔHep) mice. Finally, the predisposition to inflammation sensitivity displayed by Myd88(ΔHep) mice may be caused by the accumulation of 25-hydroxycholesterol, an oxysterol linked to inflammatory response and metabolic disorders. This study highlights the importance of MyD88 on both liver fat accumulation and cholesterol-derived bioactive lipid synthesis. These are two key features associated with metabolic syndrome. Therefore, investigating the regulation of hepatic MyD88 could lead to discovery of new therapeutic targets.